2017
DOI: 10.1051/matecconf/20179701106
|View full text |Cite
|
Sign up to set email alerts
|

Organic and Inorganic Fertilizers Application on NPK Uptake and Production of Sweet Corn in Inceptisol Soil of Lowland Swamp Area

Abstract: Abstract. This study objective was to determine the dose of organic and inorganic fertilizers which can increase N, P and K nutrients uptake as well as the growth and yield of sweet corn on inceptisol soil of lowland swamp. Inceptisol soil has low soil fertility and relatively low to moderate levels of organic matter content. Application of organic fertilizer on inceptisol soil of lowland swampis expected capable to increase N, P and K nutrients as well as yield of sweet corn. This research was conducted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
4
0
4
Order By: Relevance
“…The magnitude of nutrient uptakes and contents in sweet corn was presumably sufficient enough to support growth and development. Research conducted by Marlina et al (2017) reported that fertilizing sweet corn with 5 t/ha organic fertilizer brought about nitrogen, phosphorus and potassium uptakes as much as 16.28 mg/plant, 3 mg/plant and 12.08 mg/plant, and produced weight husked ears of 333.68 g/ plant. This number was higher than results from this experiment with average of husked ears ranged from 220.43 to 270.63 g/plant, which was still within the range of its variety description.…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of nutrient uptakes and contents in sweet corn was presumably sufficient enough to support growth and development. Research conducted by Marlina et al (2017) reported that fertilizing sweet corn with 5 t/ha organic fertilizer brought about nitrogen, phosphorus and potassium uptakes as much as 16.28 mg/plant, 3 mg/plant and 12.08 mg/plant, and produced weight husked ears of 333.68 g/ plant. This number was higher than results from this experiment with average of husked ears ranged from 220.43 to 270.63 g/plant, which was still within the range of its variety description.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the application of T. harzianum fungus significantly increased the average plant content of phosphorous by 0.358% compared to the control treatment of 0.310%. The reason is attributed to the role of the T. harzianum in dissolving phosphorous and transforming it from the form that is not available for absorption by the plant to the form available for absorption and its role in forming a dense root system that results in the efficient absorption of nutrients [21].…”
Section: The Phosphorous Content In Plants (%)mentioning
confidence: 99%
“…Trichoderma harzianum has been shown in multiple studies to aid plant growth by making more of the essential elements nitrogen, phosphorus, and potassium available to the plant. As a result of efficient nutrient uptake, the fungus is able to breakdown phosphorous and convert it to an absorbable form, all while generating a dense radical group [8]. Laws that provide for the collection of algae and identify their types and places of gathering in order to support plant species, as the specialized centers in composting have worked to find various ways to deal with the increasing quantities of algae and its organic waste, which is used as fertilizer in the agricultural field, where it is used, after drying it and then grinding it completely.…”
Section: Introductionmentioning
confidence: 99%